Zika virus modulates mitochondrial dynamics, mitophagy, and mitochondria-derived vesicles to facilitate viral replication in trophoblast cells - Lee, Jae Kyung; Shin, Ok Sarah (Frontiers in Immunology, 2023)
Zika virus (ZIKV) remains a global public health threat with the potential risk of a future outbreak. Viral infections are known to disrupt mitochondrial fitness governed by different mechanisms of mitochondrial quality control pathways. Here we demonstrate that ZIKV (PRVABC59) infection of JEG-3 trophoblast cells modulate mitochondrial dynamics, mitophagy, and formation of mitochondria-derived vesicles (MDVs). Specifically, ZIKV nonstructural protein 4A (NS4A) translocates to the mitochondria, triggers mitochondrial fission and mitophagy, and suppresses mitochondrial associated antiviral protein (MAVS)-mediated type I interferon (IFN) response. Furthermore, we performed proteomics profiling of small extracellular vesicles (sEVs) to revealed an enrichment of mitochondrial proteins upregulation of mitochondrial proteins present in sEVs secreted by ZIKV-infected JEG-3 cells, suggesting that MDV formation may also be another mitochondrial quality control mechanism manipulated during placental ZIKV infection. Altogether, our findings suggest thehighlight the different mitochondrial quality control mechanisms that are manipulated by ZIKV during infection of placental cells as host immune evasion mechanisms utilized by ZIKV at the placenta to suppress the host antiviral type I IFN response and facilitate viral infection.